2007
DOI: 10.1038/sj.clpt.6100281
|View full text |Cite
|
Sign up to set email alerts
|

Safety, Tolerability, and Pharmacokinetics of Raltegravir After Single and Multiple Doses in Healthy Subjects

Abstract: Raltegravir is a novel human immunodeficiency virus-1 integrase inhibitor with potent in vitro activity (95% inhibitory concentration (IC95)=33 nM in 50% human serum). Three double-blind, randomized, placebo-controlled, pharmacokinetic, safety, and tolerability studies were conducted: (1) single-dose escalation study (10-1,600 mg), (2) multiple-dose escalation study (100-800 mg q12 h x 10 days), and (3) single-dose female study (400 mg). Raltegravir was rapidly absorbed with a terminal half-life (t1/2) approxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
137
1
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 161 publications
(149 citation statements)
references
References 9 publications
10
137
1
1
Order By: Relevance
“…The differences observed in HIV kinetics led us to examine the sensitivity of the above cell populations to antiretroviral drugs targeting the early stages in the viral life cycle. To address this, cells were treated with zidovudine (AZT) (10 M), efavirenz (EFV) (0.1 M) (4,23,33), or the integrase inhibitors 118-D-24 (80 M) (26) and raltegravir (50 nM), which was recently approved for clinical use (8)(9)(10), at various time points postinfection. The inhibition of viral replication was assessed by quantifying intracellular p24 Gag levels 48 h postinfection.…”
Section: Kinetics Of Hiv Infection In 24-and 48-h-stimulated Cd4mentioning
confidence: 99%
“…The differences observed in HIV kinetics led us to examine the sensitivity of the above cell populations to antiretroviral drugs targeting the early stages in the viral life cycle. To address this, cells were treated with zidovudine (AZT) (10 M), efavirenz (EFV) (0.1 M) (4,23,33), or the integrase inhibitors 118-D-24 (80 M) (26) and raltegravir (50 nM), which was recently approved for clinical use (8)(9)(10), at various time points postinfection. The inhibition of viral replication was assessed by quantifying intracellular p24 Gag levels 48 h postinfection.…”
Section: Kinetics Of Hiv Infection In 24-and 48-h-stimulated Cd4mentioning
confidence: 99%
“…These results indicate our newly developed method achieves the same level of reproducibility and accuracy as the LC-MS/MS method. As plasma concentrations of raltegravir are expected in the 0.01 to 4.71 mg/ml range when raltegravir is administered at single dose of 400 mg, [16][17][18] our method successfully covers this region with good precision and accuracy. Actually, the raltegravir concentration change was clearly demonstrated; it rose from 1.2 (0 h) to 5.2 mg/ml (1 h), then decreased to 1.5 mg/ml (6 h) when raltegravir was orally administered 400 mg twice daily in an HIV-1-infected patient.…”
Section: Discussionmentioning
confidence: 99%
“…When raltegravir is administered by a single 400 mg dose, plasma concentrations are expected in the 0.01 to 4.71 mg/ml range. [16][17][18] In this study, raltegravir concentrations at steady state following multiple-dose administration ranged from 1.2 to 5.2 mg/ml.…”
Section: Lc-ms Chromatogramsmentioning
confidence: 99%
“…Singledose escalation studies over a dose range of 10-1200 mg of raltegravir demonstrated approximately dose-proportional increases in AUC and plasma concentrations. 17 Raltegravir was rapidly absorbed, and time to peak plasma concentrations were between 0.5 to 1.3 h. A biphasic decline in plasma concentrations was observed with an apparent half-life of initial phase of 1 h and a terminal phase half-life of 7-12 h. Raltegravir dose of 200 mg or higher achieved C 12 h concentrations greater than the protein-adjusted IC 95 value of 33 nM. Key pharmacokinetic parameters of raltegravir at 200 and 400 mg doses are summarized in Table 2.…”
Section: Pharmacokinetics and Metabolismmentioning
confidence: 99%